[tex]\bf a^{\frac{ n}{ m}} \implies \sqrt[ m]{a^ n}
\qquad \qquad
\sqrt[ m]{a^ n}\implies a^{\frac{ n}{ m}}
\\\\\\
a^{-\frac{ n}{ m}} \implies
\cfrac{1}{a^{\frac{ n}{ m}}} \implies \cfrac{1}{\sqrt[ m]{a^ n}}
\qquad\qquad
% radical denominator
\cfrac{1}{\sqrt[ m]{a^ n}}= \cfrac{1}{a^{\frac{ n}{ m}}}\implies a^{-\frac{ n}{ m}}
\\\\
-------------------------------\\\\
2y^{-\frac{2}{7}}\implies 2\cdot \cfrac{1}{y^{\frac{2}{7}}}\implies 2\cdot \cfrac{1}{\sqrt[7]{y^2}}\implies \cfrac{2}{\sqrt[7]{y^2}}[/tex]